PENGARUH KUALITAS WEBSITE “PEJABAT PENGELOLA INFORMASI DAN DOKUMENTASI (PPID)” TERHADAP KEPUASAN PENGGUNA DI DINAS KOMUNIKASI DAN INFORMATIKA KABUPATEN PEMALANG - ardieansyah ardieansyah (Institut Pemerintahan Dalam Negeri (IPDN), 2022)
In the current era of globalization, the use of information technology is very much needed by the community, In Indonesia, including in Pemalang Regency, the delivery of information from the government to the community is one of them by utilizing the Information Management and Documentation Officer (PPID) website which has the function of providing information from various Regional Apparatus Organizations (PPID). OPD) which can be downloaded by the public. This study aims to determine the benefits of the PPID website as measured by the influence of the quality of the PPID website on website user satisfaction. With the PPID website, it is necessary to do research on the quality of the website. In this study, website quality analysis was carried out using the Webqual 4.0 model according to Barnes and Vidnes (2003) with three variables namely usability quality, information quality, and service interaction quality which will be tested for the effect of website user satisfaction according to the user satisfaction theory by Doll and Torkzadeh (Dasgupta 2014). This study uses a quantitative method by taking a population from a list of information downloaders through the PPID website in Pemalang Regency with a sample of 40 downloaders and collecting data using an online questionnaire and from the results of documents collected by the author based on data taken from the Communication and Information Office of Pemalang Regency. The results of the questionnaire were processed using SPSS version 21. Data analysis used multiple linear regression analysis. Based on the results of the analysis, the conclusions that can be drawn are that the quality of usability, the quality of information, and the quality of service interactions have a simultaneous effect on the satisfaction of PPID website users. However, partially the quality of usability and the quality of information have no significant effect on the satisfaction of PPID website users. Partially, only the quality of service interaction affects the satisfaction of PPID website users.